Wood Frog eDNA Survey Results - Spangler, Mark A.; Huettmann, Falk; Herriott, Ian C.; López, J. Andrés (Dryad Digital Repository, 2017)
1 liter water samples collected around Fairbanks/North Pole for eDNA analysis. Filters were cut in half and DNA isolated via phenol-chloroform from one half. Other half is archived. qPCR (SYBR Green) conducted for detection of wood frog cytB (Rasy_00)..